Energy poverty and social assistance in the Brussels-Capital Region - Anne Baudaux; Françoise Bartiaux (Brussels Studies, 2020)
This ethnographic contribution focuses on energy poverty and aid policies in the Brussels-Capital Region. The data produced between 2014 and 2017 consist of field observations and in-depth interviews with people affected by energy poverty. Our study shows that the practices and negative emotions of these people must be understood in the context of the shortage of modest housing in the Brussels Region and the poor state of the housing stock. This context is hardly taken into account by public aid, which insists instead on the technical equipment to be installed in homes and on changes in the individual behaviour of occupants. These differences in perspective and the sometimes stigmatising or condescending bureaucratic aid practices help explain the limited use of aid intended to fight energy poverty.